PENGEMBANGAN MEDIA POP - UP BOOK UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS V MI MA’ARIF AT TAQWA KESAMBEN KULON WRINGINANOM GRESIK - Asyifa, Salsa Ade Nisa; Fithriyah, Ainul (Jurnal Muassis Pendidikan Dasar, 2024)
This study aims to develop a Pop-Up Book-based learning media to enhance critical thinking skills of fifth-grade students at MI Ma’arif At Taqwa in social studies, particularly in the topic of cultural diversity in Indonesia. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The media was validated by content and media experts, achieving feasibility percentages of 91.67% and 98.33%, respectively. A limited trial with 10 students showed a highly positive response with an average score of 4.39 (87.87%), categorized as "very good". The analysis of pre-test and post-test results indicated a significant improvement in students' critical thinking skills. The Pop-Up Book media proved to be effective, engaging, and contextually relevant, supporting integrative thematic learning and reinforcing the values of the Pancasila Student Profile. This research recommends the media as an innovative and feasible alternative for teaching social studies in elementary schools.